Kajian Potensi Flying Rock Peledakan Terhadap Radius Aman Alat Peremuk Crusher di CV Tekad Jaya Halaban Kabupaten Lima Puluh Kota Sumatera Barat - Randa Ramadhan; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Flyrocks is a situation where a miss occurs due to a problem when blasting occurs. Some things that might cause a flyrock are no free face, inappropriate stemming, shallow holes and too many rows. It is expected that with the appropriate geometry can minimize the impact of flyrock that occurs during blasting because it can endanger the tools, buildings and humans that are around the blasting. The research location is in CV Tekad Jaya. The study was conducted by measuring the actual maximum throw distance of the flyrock in the field. Observations were made 35 times. Estimated flyrock throw distances use two methods namely Richard and Moore's theory (2005) to see the impact of stemming and burden on flyrock and Abraham Ghasemi (2012) to see the impact of PF on flyrock. From the estimation results a new geometry was designed using the RL Ash and CJ Konya methods to get a new geometry that has a minimum flyrock. Then obtained nominal burden, stemming and PF of 1.9; 1.43; 0.494 for RL Ash and 2.2; 1.7; 0.397 for CJ Konya. With the geometry obtained flyrock throw distance between 12m to 40m which can be said to be safe for the company.Keywords: Blasting, Flyrock, Geometry, RL Ash, CJ Konya